Parametrizability of infinitely generated attractors - Shaw, Eve; Vellis, Vyron (Annales Fennici Mathematici, 2024)
An infinite iterated function system (IIFS) is a countable collection of contraction maps on a compact metric space. In this paper we study the conditions under which the attractor of such a system admits a parameterization by a continuous or Hölder continuous map of the unit interval.